Effect of carbon nanoparticles in enhancing the vegetative propagation of Orthosiphon aristatus - Dhivya Viswanathan; Ranjani Soundhararajan; Hemalatha Srinivasan (Discover Sustainability)
Abstract Nanomaterials are being greatly used in the agriculture sector to address a variety of problems including soil erosion, non-bioavailability of nutrients, pest infestation, and climate change. In this study, the peel waste of commonly available banana variety in southern India Musa acuminata was used for synthesizing carbon nanoparticles and this article focusses on analyzing the effects of carbon nanoparticles (CNPs) in assisting the vegetative propagation of Orthosiphon aristatus. The effect of synthesized CNPs on the plant phenotype were examined for growth metrics including the number of new leaves formed, increase in aerial height of stem cuttings, number of nodes, leaf area, and root length. In addition, biochemical constituents including tryptophan, protein, and carbohydrate levels and photosynthetic pigments including chlorophylls and carotenoids were quantified. The treated stem cuttings at 5% CNPs had the highest increase in shoot length (7.35 cm) and more new leaves were observed (5.77) and the highest root length was also observed in the stem cuttings exposed to 5% CNPs (3 cm). Plants treated with CNPs showed a significant rise (p < 0.05) in the levels of carotenoid and chlorophyll and the highest rise in total chlorophyll content was observed in stem cuttings exposed to 10% CNPs (0.86 mg/g). Thus, this work gives a comprehensive understanding of developing value-added products (CNPs) from commonly discarded wastes and the effect of CNPs on plants’ phenotype and physiology, opening the road for sustainable agricultural practices.